Effect of Surface Functionalization of MCM-41-Type Mesoporous Silica Nanoparticles on the Endocytosis by Human Cancer Cells - Igor I. Slowing; Brian G. Trewyn; Victor S.-Y. Lin (2006)
We have synthesized a series of MCM-41-type mesoporous silica nanoparticles (MSN). The surface of the MSNs are functionalized with 3-aminopropyl (AP), 3-guanidinopropyl (GP), 3-[N-(2-guanidinoethyl)guanidino]propyl (GEGP), and N-folate-3-aminopropyl (FAP). In contrast to the ζ-potential of −18.4 mV for FITC-MSN, the values of ζ-potential for AP-, GP-, GEGP-, and FAP-functionalized FITC-MSNs in 100 mM PBS buffer (pH 7.4) increased positively from −11.3, −10.6, −4.0, to +4.9 mV, respectively. The uptake efficiency, endocytosis mechanism, and biocompatibility of these organically functionalized MSNs were investigated with human cervical cancer cells (HeLa). Flow cytometry results suggested that the endocytosis of MSN could be manipulated by different surface functionalization. The immunocytochemistry study indicated that the uptake of these MSNs by HeLa cells was surface functional group dependent and involved several different mechanisms of endocytosis. Confocal fluorescence micrographs showed that the different surface functionalities of MSNs could also affect their ability to escape endosomal entrapment, which is a key factor in designing effective intracellular delivery vehicles.